2020
DOI: 10.1101/2020.09.22.20199125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Architecture of Early Dissemination and Massive Second Wave of the SARS-CoV-2 Virus in a Major Metropolitan Area

Abstract: We sequenced the genomes of 5,085 SARS-CoV-2 strains causing two COVID-19 disease waves in metropolitan Houston, Texas, an ethnically diverse region with seven million residents. The genomes were from viruses recovered in the earliest recognized phase of the pandemic in Houston, and an ongoing massive second wave of infections. The virus was originally introduced into Houston many times independently. Virtually all strains in the second wave have a Gly614 amino acid replacement in the spike protein, a polymorp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 114 publications
(104 reference statements)
3
93
1
Order By: Relevance
“…Long et al sequenced the genomes of 5,085 SARS-CoV-2 strains causing COVID-19 waves in an ethnically diverse population of Houston in the USA. They concluded that most of the strains in the second wave were having a Gly614 amino acid replacement in the spike protein, which could be linked to increased transmission and infectivity [11]. The findings also help in delineating the origin and trajectory of subsequent infection waves.…”
Section: The Multiple Strains Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Long et al sequenced the genomes of 5,085 SARS-CoV-2 strains causing COVID-19 waves in an ethnically diverse population of Houston in the USA. They concluded that most of the strains in the second wave were having a Gly614 amino acid replacement in the spike protein, which could be linked to increased transmission and infectivity [11]. The findings also help in delineating the origin and trajectory of subsequent infection waves.…”
Section: The Multiple Strains Of Sars-cov-2mentioning
confidence: 99%
“…Though, the new G-strain, which is increasingly affecting populations of various countries, seems to be more contagious [10]. The new G-strain evolved as the result of a mutation known as D614G, has gradually replaced the D strain all over the world and now accounts for over 85% of published SARS-CoV-2 genomes [11]. In the new G-strain there is supplementation of aspartic acid (D) in the 614th position of the amino acid with glycine (G), hence, named as D614G.…”
Section: The Multiple Strains Of Sars-cov-2mentioning
confidence: 99%
“… 217 However, mutagenicity observed with the virus poses current challenges of specificity for use of monoclonal antibodies, and extensive studies are warranted. 218 However, considering the current developments in the field of radiopharmaceuticals, it is worth the effort and research is underway for development of diagnostic/theranostic agent.…”
Section: Radionuclides and Covid-19mentioning
confidence: 99%
“…Virtually all strains in the second wave have a Gly614 amino acid replacement in the spike protein, a polymorphism that has been linked to increased transmission and infectivity. Patients infected with the Gly614 variant strains had significantly higher virus loads in the nasopharynx on initial diagnosis and found no link between disease incidence, mortality, ethnicity, and virus clades 87,88 . The scientific community around the world must be alert and ready to learn the sources, structure, and mechanism of possible waves of infections, along with the possible effects on SARS CoV‐2 production, and any related host immune response and therapeutic strategies 89 …”
Section: Scientific Collaborations Multidisciplinary Research and Gmentioning
confidence: 99%